Melawi Malay Medicine Mantras As A Medium Of Religious Communication - Winda Afriani; Martono; Sesilia Seli; Antonius Totok Priyadi; Agus Wartiningsih; Ikhza Mahendra Putra (INJECT (Interdisciplinary Journal of Communication), 2026)
Mantras in the Malay oral tradition function not only as a means of traditional medicine but also as a medium of religious communication that transmits Islamic values through local cultural symbols. This study aims to analyze how Melawi Malay medicine mantras function as a medium of religious communication in conveying religious messages to the community. The study employed a qualitative-descriptive approach through text analysis and cultural interpretation of six traditional medicine mantras of the Melawi Malay community in West Kalimantan. The analysis was conducted using Paul Ricoeur’s cultural hermeneutics, Bronislaw Malinowski’s anthropological approach, and the perspective of cultural communication to understand the relationship among ritual language, local symbols, and religious messages within the mantras. Data were collected through interviews, observation, recordings of mantra recitations, and transcription using the International Phonetic Alphabet (IPA). The findings indicate that the mantras contain strong elements of religious communication through the use of declarations of tawhid, the mention of Allah, the Prophet Muhammad, and religious prayers integrated with natural symbols, local cosmology, traditional magical elements, and relationships between humans and nature. These findings demonstrate that mantras function not only as a medium of healing but also as a medium of religious communication that enables Islamic values to be communicated and internalized through local cultural structures that already possess social legitimacy within the community. This study contributes to the development of religious communication and cultural communication studies by demonstrating that oral traditions can serve as a medium for conveying religious messages within traditional societies.